PEMBINAAN TARTIL AL-QUR’AN METODE TILAWATI DI IBU - IBU AISYIYAH RANTING JOGODALU BENJENG GRESIK - Muyasaroh Muyasaroh (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This dedication is motivated by the urgency of reading the Qur'an as part of Muslim worship« وَاٌلَذِي يَقُراٌ القُرانَ وَيَتَتَعتَعُ فِيه وَهُوَ عَلَيهِ شَاقٌ لَه اَجَران » متفقٌ عليهRasulullah said,